ECOSUSTAINABLE HIGH-RISE : The Environmentally Conscious Architecture of Skyscraper - Jimmy Priatman (DIMENSI (Journal of Architecture and Built Environment), 2000)
The term " green architecture " is related to evolving architecture which is sensitive to the environment and emerges from the environmental awareness due to the effects of destruction of air, water, energy and earth. It is characterized by improving energy efficiency, sustainability concept and holistic approach of the entire building enterprise, where all of the environmental factors are regarded as an objective. Although there are many of environmentally conscious architectural works today, but most of the building designers prefer to deal primarily with small-scale buildings (low to medium rise) and often only in greenfield, rural or suburban sites. All those large scale, high-rise or tall buildings located in dense urban areas are regarded as avoidable objects that consumes a lot of energy, uses huge amounts of materials, and produces massive volumes of waste discharge into the environment. These intensive buildings deserve greater attention and should be designed by greater part of our expertise and effort to ecologically design than the smaller buildings with fewer problems. The paper discusses "green" dimensions applied to tall buildings/high-rise buildings with their innovative approach that leads to ecosustainable tall buildings.